The relationship between TLR4 gene polymorphism (rs7873784) and urinary tract infections caused by multidrug-resistant bacteria among Iraqi patients - Radhi, Akram; SEÇİL AKILLI ŞİMŞEK ‎ (University of Thi-Qar Journal of Science, 2025)
Toll-Like Receptor 4 (TLR4) is a pattern recognition receptor (PRR) that identifies pathogen-associated molecular patterns (PAMPs) molecules found on the surface of bacteria, viruses, and other pathogens. This study aimed to evaluate the relationship between functional gene polymorphisms (TLR4-rs7873784) and susceptibility to multidrug-resistant (MDR) bacteria in urinary tract infections (UTIs). A total of 350 urine samples were collected from males and females aged 10–75 years at Al-Rifae General Hospital in Thi-Qar province, southern Iraq, between July 2022 and January 2023. All bacterial isolates were identified biochemically and by VITEK-2 system then confirmed with 16SrRNA gene. Resistance genes were detected using bacterial colonies in a PCR test. Tetra-ARMS-PCR was used to detect TLR4 gene polymorphism (rs7873784).150 samples (42.9%) showed positive bacterial growth, while 200 samples (57.1%) were culture-negative. The samples that were positive for bacterial growth were 150 samples, including 30 XDR samples, 20 sensitive to antibiotics, and 100 MDR samples, pathogens isolated MDR included Escherichia coli (44%), Staphylococcus aureus (33%), Klebsiella pneumoniae (10%), and Proteus mirabilis (13%). Regarding resistance genes: BlaCTX-M was detected in 81.8% of E. coli, 100% of K. pneumoniae, and 30.8% of P. mirabilis; BlaSHV in 29.5% of E. coli, and 100% of both K. pneumoniae and P. mirabilis; BlaAMPC in 90.9% of E. coli, 100% of K. pneumonia, and 30.8% of P. mirabilis; and BlaTEM in all Gram-negative isolates.